1981
DOI: 10.2118/9975-pa
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Evaluation With Pressure Transient Testing in Low-Permeability Gas Reservoirs

Abstract: This paper presents theoretical and practical aspects of methods used to determine formation permeability, fracture length, and fracture conductivity in low-permeability, hydraulically fractured gas reservoirs. Methods examined include Horner analysis, linear flow analysis, type curves, and finitedifference reservoir simulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Lee and Holditch (1981) presented an analysis of effective fracture length from hydraulically-fractured, low permeability reservoirs. The results indicated that effective fracture length averaged only 5 % to 11 % of the designed length.…”
Section: Introductionmentioning
confidence: 99%
“…Lee and Holditch (1981) presented an analysis of effective fracture length from hydraulically-fractured, low permeability reservoirs. The results indicated that effective fracture length averaged only 5 % to 11 % of the designed length.…”
Section: Introductionmentioning
confidence: 99%
“…It becomes more complex in the presence of water, oil, and gas that may require three-phase flow model. It is always recommended to perform the PBU analysis on wells which are planned to be stimulated prior to the stimulation to assess the formation properties (Lee and Holditch 1981;Holditch 1979;Soliman and Hunt 1985). This was not possible in this case, since the well did not flow after perforation.…”
Section: Figure 6c-ratio Between Peak 1 and Peak 2 Heights For Well-cmentioning
confidence: 99%
“…4 It is well known that analyzing post-fracture pressure transient tests can be very difficult. Even if only a single-phase fluid is flowing, the analysis ofthe data can be complicated.…”
Section: 3mentioning
confidence: 99%